Response behaviour in wintering wigeon (Mareca penelope) due to motor/electric boat disturbance: explorative data suggest a recurrent pattern (Avocetta, 2020)
The behavioural response of a wintering focal flock of Wigeon Mareca penelope in relation to the periodic passage of the motor/ electric boats was studied during an Environmental Impact Assessment. A recurring escape model emerged. At each passage of the boats, birds resting in the fields along the lake banks first flew to the neighbouring waters (averaged escape distance: 116.6 m ± 25.8), then (ii) flew away, (iii) returned in the waters (near the banks) and, finally, (iv) returned in the neighbouring fields. These first data could stimulate further research on the escape behaviour from this anthropogenic disturbance.
Keywords: anthropogenic disturbance; escape distance; recurrent escape model; threat analysis